Perspectives and lived experiences of survivors and caregivers of COVID-19 patients in a teaching hospital in a tribal district of Chhattisgarh, India - Shilpa Khanna; Shriyuta Abhishek; Mohammad Shagill; Lakhan Singh; Chetanya Malik; Savithri Devi; T Priyadarsh; Yogeshwar Kalkonde (Journal of Family Medicine and Primary Care)
Background The rural–urban healthcare disparity in India was exacerbated during the COVID-19 pandemic, with the second wave hitting rural areas particularly hard due to weak infrastructure. A study in Chhattisgarh aims to explore the experiences of severely ill COVID-19 survivors and caregivers to inform patient-centric care delivery in primary settings. Methods In this qualitative study, we conducted in-depth interviews with seven patients and seven caregivers during home visits or telephonically to understand lived experiences of receiving care for COVID-19 in an ICU in the public health system. Socioecological model was used to guide the qualitative inquiry. Results COVID-19 patients faced stigma due to their diagnosis. The survivors felt lonely due to isolation, uncertainty about their illness, and fear of death. Poor mental health during ICU stay affected their physical health. Patients with caregivers felt supported despite visitor restrictions. Transparent communication with health providers reduced distress. Conclusion The study in Chhattisgarh, India, highlights ICU survivors’ and caregivers’ experiences, revealing fear and loneliness among patients. Effective communication and caregiver presence improve outcomes, emphasizing holistic support. There’s an urgent need for palliative care integration, caregiver inclusion, and comprehensive post-discharge follow-up by primary-level practitioners in rural settings. Lack of state-level palliative care policy emphasizes the need for comprehensive initiatives to enhance healthcare outcomes.